2016
DOI: 10.1080/00223891.2016.1238829
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the MMPI–2–RF Triarchic Psychopathy Scales in Correctional and Collegiate Samples

Abstract: This study examined the MMPI-2-RF (Ben-Porath & Tellegen, 2008/2011) Triarchic Psychopathy scales recently developed by Sellbom et al. ( 2016 ) in 3 separate groups of male correctional inmates and 2 college samples. Participants were administered a diverse battery of psychopathy specific measures (e.g., Psychopathy Checklist-Revised [Hare, 2003 ], Psychopathic Personality Inventory-Revised [Lilienfeld & Widows, 2005 ], Triarchic Psychopathy Measure [Patrick, 2010 ]), omnibus personality and psychopathology me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The association of APM-2 Meanness with dangerous thrill-seeking as seen in this study is consistent with findings that the MMPI-2-RF (Ben-Porath & Tellgen, 2008) triarchic Meanness scale was significantly associated with a measure of risk taking (Kutchen et al, 2017), and MPQ-based Meanness was significantly associated with a sensation seeking scale (Brislin et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association of APM-2 Meanness with dangerous thrill-seeking as seen in this study is consistent with findings that the MMPI-2-RF (Ben-Porath & Tellgen, 2008) triarchic Meanness scale was significantly associated with a measure of risk taking (Kutchen et al, 2017), and MPQ-based Meanness was significantly associated with a sensation seeking scale (Brislin et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Hall et al (2014) found that PPI-Meanness and PPI-Disinhibition contributed equally to the prediction of MPQ Aggression in a regression analysis. Kutchen et al (2017) found the MMPI-2-RF Disinhibition scale, along with the Meanness scale, to be a significant predictor of measures of aggression. Further, Patrick (2018) notes, albeit with respect to violent offenders, that some persons display aggressive tendencies mostly as an expression of anger and weak restraint associated with disinhibition, while others display aggressive behavior primarily resulting from lack of sensitivity, a low level of social concern, and predatory goal seeking associated with meanness.…”
Section: Discussionmentioning
confidence: 85%
“…The MMPI-2-RF (Ben-Porath & Tellegen, 2008/2011) was scored from MMPI-2 (Butcher et al, 2001) administrations, which has been supported empirically in this context (Tarescavage, Alosco, Ben-Porath, Wood, & Luna-Jones, 2015). To operationalize the triarchic model, we used the MMPI-2-RF Triarchic scales (Sellbom et al, 2016), which have been well validated in a range of university, community, and correctional samples (Anestis et al, 2018;Gottfried et al, 2019;Kutchen et al, 2017;Sellbom et al, 2016). Cronbach's alphas were .78 (male) and .81 (female) for Boldness, .80 and .81 for Meanness, and .72 and .68 for Disinhibition.…”
Section: Methodsmentioning
confidence: 99%
“…Psychopathy is a clinical construct with substantial overlap with the personality characteristics of antisocial personality disorder (ASPD) from the Diagnostic and Statistical Manual of Mental Disorders (Skeem et al, 2011). The construct has been validated using several factors across offending and nonoffending samples (Kutchen et al, 2017) and across cultures, including Europe and China (Seara-Cardoso et al, 2020; Shou et al, 2017). Psychopathic personality traits (PPTs), which encompass aspects of callous and unemotional traits, narcissism, and disinhibition, have been implicated in a host of detrimental developmental and life outcomes ranging from increased behavioral maladaptation to risk-seeking and offending behavior (Hare & Hart, 1993; Vaughn et al, 2008).…”
Section: Psychopathic Personality Traitsmentioning
confidence: 99%